Basic Dye (Metyhl Red) removal from simulated wastewater by adsorption using treated sugarcane bagasse - Saiful Azhar, Saad; Azlinda, Abdul Ghani; Farizul Hafiz, Kasim; Suhardy ,Daud; Mohd Nazry, Salleh (Kolej Universiti Teknologi Tun Hussein Onn (KUiTTHO), 2008)
Organized by Kolej Universiti Teknologi Tun Hussein Onn (KUiTTHO), 18th – 20th December 2006 at Batu Pahat, Johor.